Hearbal Detox Extract Formulation From Seven Wonderful Natural Herbs: Garlic, Ginger, Honey, Carrots, Aloe Vera, Dates, & Corn - Saleh, Mohammed Yerima; Chaturvedi, Saurabh; Ibrahim, Bello; Khan, Mohammed Shahid; Jain, Harshita; Nama, Nitin; Jain, Vikas (Asian Journal of Pharmaceutical Research and Development, 2019)
The current mode of treatment of various diseases that cause as result of tobacco products based on synthetic drugs is very expensive, insalubrious and also not obtainable to all patients, at the same time these drugs alters genetics and metabolic pathways and also shows great adverse side effects to many patients. Hence, a safe and effective alternative natural remedy is needed to prevent the disease development and progression. In this lookout, natural recipes are indeed healthy and good remedy in the treatment/management of diseases that cause as result of tobacco products and these natural herbs are affordable, accessible and effective without any adverse side effects. These seven wonderful natural recipes (Garlic, ginger, honey, carrots, aloe Vera, dates & corn) are considered to be the most significant ancient herbs that have been used as an herbal remedy for over 2500 years all over the world. Although this research is first of its kind, because there was no such research conducted by any researcher who combined these seven wonderful natural recipes as a therapeutics, however there were several similar earlier studies on one or combination of either these recipes which have shown a very remarkable and suitable alternative remedy in various diseases cure without any side effects. This juice extracts from seven wonderful natural recipes are of paramount important with an immense medical properties and health beneficial effects that treats cancer further complications, cleanse the nicotine & tar from lungs that cause as a result of tobacco uses, boost immune system, as well as serve as an antibiotic in the remedy of many ailments.